Mechanical Assisted Modification of Halloysite Nano Clay: Characterization and Its Effect on Mechanical Properties of Halloysite-Epoxy Nano Composites - Rudresh, M.; Maruthi, B. H.; Nagaswarupa, H. P.; Surendra, B. S.; Anil Kumar, M. R.; Raghavendra, N. (Asian Journal of Engineering and Applied Technology, 2019)
Modificationof Halloysite nano clay has been done using 3-aminopropyltriethoxysilane in the presence of distilled water as solvent media. Untreated and modified nano clay was characterized by Powder X-ray diffractometer (PXRD), Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FT-IR). Functionalization of Halloysite nano clay is also strongly affected the morphological parameters and enabling the application in epoxy nano composite. However, the influence of modified clay concentration on the mechanical properties of epoxy/nanoclay composites, with different concentrations (2%, 3%, 4% and 5%) of nano clay in the epoxy resin was investigated. Experimental results showed that the mechanical properties of epoxy were improved upto 4 wt% of HNP’s, evidently because of the loading of modified clay. The tensile strength, tensile Modulus, flexural strength, flexural modulusand fracture toughness of the nanocomposites increased by 13%, 17%, 9%, 14%and 27% respectively this demonstrated that the composites were strengthened.